Juridical Analysis of the Application of Restorative Justice at the Prosecution Stage of Petty Theft Crime - Muhammad Ridwan Lubis (ISNU Nine-Star Multidisciplinary Journal, 2024)
Indonesia continues to strive to ensure that the law implemented for its citizens is rooted in the values that live and develop within society. If applied, this legal entity will make the community feel comfortable and familiar with its legal model. Restorative justice is a resolution for criminal cases that involves the offender, the victim, the families of both parties, and other related parties to collectively seek a fair solution, emphasizing restoration to the original state rather than retribution. Law No. 11 of 2021 concerning Amendments to Law No. 16 of 2004 regarding the Attorney General of the Republic of Indonesia states that one of the authorities of the Attorney General is to dismiss cases in the interest of the public. The Attorney General has found many inconsistencies in the existing criminal justice system; therefore, in this context, "public interest" refers to the interests of the nation and state and/or the interests of the broader community. This research was conducted using a normative juridical research method, with data collection carried out through literature studies. The research specification used is descriptive qualitative. This study aims to examine how restorative justice applies to minor criminal offenders, such as theft, at the prosecutorial level, and how restorative justice is implemented for minor criminal offenders in theft cases at the Pangkalpinang District Attorney's Office, particularly in the case of the termination of prosecution through the Decree of Termination of Prosecution by the Pangkalpinang District Attorney No. 01/L.9.10.3/Eoh.2/01/2022 dated January 13, 2022.